Comparing Basic Words and Using Lexicostatistics to Identify Language Connections among Indonesian, Dayak Ngaju, and Javanese - Tri Aprilia Suciati; Imam Qalyubi; Misrita (ENGLISH JOURNAL OF INDRAGIRI, 2026)
This study discusses the degree of kinship between Indonesian, Dayak Ngaju, and Javanese languages using a lexicostatistical approach. This method is employed to determine the linguistic relationships based on the number of basic vocabulary items that share similarities in form and meaning. Based on data from 15 glosses, the results show a 100% cognate rate among the three languages, indicating a strong historical connection as part of the Austronesian language family.